Women’s human agency and self-determination in Guatemalan tourism development - Lindsay Usher; Duarte B. Morais (PASOS Revista de Turismo y Patrimonio Cultural, 2010)
Tourism is often identified as a strategy to ameliorate the wellbeing of poor communities and their most vulnerable members – women and their children. Women’s ability to get involved in and benefit from tourism is, however, conditioned by traditional gender roles and consequent education handicaps. Development programs often target women to mitigate these disparities. Thispaper examines whether an intervention by the Peace Corps resulted in improved human agency and self-determination among indigenous Q’eqchi’ women in Alta Verapaz, Guatemala. The paper reports the accomplishments and shortcomings of the intervention and elaborates on the practical and theoretical implications of the findings.